Effects of repeated prenatal ultrasound examinations on childhood outcome up to 8 years of age: follow-up of a randomised controlled trial - Newnham, J.; Doherty, D. A.; Kendall, Garth; Zubrick, Stephen; Landau, L.; Stanley, F. (Lancet Publishing, 2004)
Despite the widespread use of prenatal ultrasound studies, there are no published data from randomised controlled trials describing childhood outcomes that might be influenced by repeated ultrasound exposures. We previously undertook a randomised controlled trial to assess the effects of multiple studies on pregnancy and childhood outcomes and reported that those pregnancies allocated to receive multiple examinations had an unexplained and significant increase in the proportion of growth restricted newborns. Our aim was to investigate the possible effects of multiple prenatal ultrasound scans on growth and development in childhood. Here, we provide follow-up data of the childrens' development.